Hajdu Cheney Syndrome - Samuel, Shini Susan (J Clin Diagn Res, 2016)
Hajdu-Cheney Syndrome is a rare genetic disorder characterised by progressive focal bone destruction. It is known to be an autosomal dominant disorder but there have been reports of sporadic cases as well. Although the disease manifestation is found to begin from birth, it is most often not diagnosed until adolescence or adulthood. It could be due to the rarity of the condition and the variation of the disease manifestation at different age groups. We report a case of Hajdu-Cheney Syndrome in a 26-year-old male who presented with severe periodontitis and premature loss of teeth. The other characteristic features included craniofacial dysmorphism, abnormalities of the digits and dental anomalies. Patients with craniofacial dysmorphism along with dental abnormalities should be thoroughly examined for any underlying systemic disorder. A team of specialists may be able to diagnose this condition before the disease is advanced.